The Effects of Teaching Technique and Self-Esteem Towards Students’ Speaking Skill in Undergraduate English Department - Latifah, Latifah (CV. Pena Persada, 2018)
The purpose of this research is to find out the effects of teaching technique towards students‘ speaking skill. To find out the effects of self-esteem towards students‘ speaking skill. And then to find out the interaction effects of teaching technique and self-esteem towards students‘ speaking skill. The method used is experiment. The samples were taken from 40 students with a random technique. The data was collected by doing experiment to the sample students by using dialogue technique, distributing questionnaires on students‘ self-esteem towards speaking skill, and test for speaking skill. The data was analyzed by using two ways variant (ANOVA) to test the differences of the average score with two independent variables. This research was conducted from September 2017 up to January 2018. The result shows that there is significant effect of Teaching Technique towards Students‘ Speaking Skill (Fo = 30,068 and Sig. = 0,000 < 0,05). There is significant effect of SelfEsteem towards Student‘s Speaking Skill (Fo = 21,979 and Sig. = 0,000 < 0,05). There is no significant interactive effect of Teaching Technique and Self-Esteem towards Students‘ Speaking (Fo = 3,215 and Sig. = 0,077 > 0,05).